RETRACTED: Combing Effects of Economic Development and Globalization Towards Energy Efficiency and Environmental Degradation: Fresh Analysis From Energy Efficient Resources - Tang, Jinquan (Frontiers in Energy Research, 2022)
How much environmental pollution can be reduced by the efficient use of financial, natural, and energy resources in the current globalization. Thus, this study provides empirical evidence in support of the theoretical argument by investigating the impact of financial development, environmental assets, globalization, coal, natural gas, and sustainable carbon emissions in 32 developed countries from 1990 to 2016. Ecological degradation (estimated by carbon dioxide emissions) experienced a structural shift that was considerably more pronounced in 2000–2011 than in 1991–1998. A broad variety of econometric methodologies (such as the Chow test, Cross- country regression, and the Generalized Method of Moments (GMM)) were applied. As a consequence, environmental deterioration is strongly linked to economic development and urbanization, according to the findings. These nations' ecological footprints are favorably influenced by financial development, environmental assets, and non-renewable energy, whereas globalization and sustainable sources have a negative impact. Environmental degradation may be slowed by combining globalization's impact on financial growth with the conservation of natural resources such as renewable energy sources. In order to improve their economic and ecological resource frameworks, these nations will need to increase their use of solar and other renewable energy.